Analisis Struktur Modal dalam Meningkatkan Profitabilitas Perusahaan (Studi Kasus pada PT. Aneka Tambang ANTAM Tbk) - Silvia Nur Aisyah; Maslichah Maslichah; Irma Hidayati (Universitas Islam Malang, 2023)
One of the company's benchmarks in assessing financial performance is to produce high profitability. Profitability is an important factor in determining long-term company strategy decisions. This study aims to analyze the relationship between the company's capital structure and the level of profitability at PT. Aneka Tambang (ANTAM) Tbk. Capital structure measurement in this study using the ratio Debt Asset ratio (DAR) and Debt Equity Ratio(DER), meanwhile measurement of profitability uses the ratio of Return on Assets (ROA) and Return on Equity (ROE). The approach used in this research is a quantitative descriptive approach. The data analysis technique used is descriptive analysis. The data used is secondary data. Based on the results of the research conducted, it is known that a combination of balanced equity and debt and the use of funding sources have a significant effect on PT. Aneka Tambang (ANTAM) profitability. As for 2019 PT. Aneka Tambang (ANTAM) Tbk tends to experience a decline due to the impact of COVID- 19 which results in a decrease in market demand and fluctuations in the company's income that are not optimal. This research has implications for the management of PT. Aneka Tambang (ANTAM) Tbk in optimizing the company's capital structure to achieve higher profitability by increasing operational efficiency and considering the right level of leverage, so that the company achieves better financial performance.Keywords : Profitability, return on assets, return on equity, capital structures, debt to equity ratio, debt to assets ratio.